Structural dimensions and their changes in a reentrant hexagonal-lamellar transition of phospholipids. - Rand, R P (1994)
A hexagonal-lamellar-hexagonal (HII-L-HII) reentrant phase transition sequence on dehydration of dioleoylphosphatidylethanolamine occurs below 22 degrees C. This provides an unusual opportunity to measure how several structural dimensions change during this transition. Using x-ray diffraction, we have measured these dimensions with a hope of gaining some clue about the accompanying internal stresses. The principal dimensions described are molecular areas and molecular lengths projected onto the hexagonal lattice. In contrast with large changes in average area at the polar and hydrocarbon ends of the molecule, a position near the polar group/hydrocarbon interface is one of constant molecular area. It remains constant both as the monolayers curl from changing water content and in the transition from one structure to the other. In the L-to-HII transition, the most obvious change in molecular length is a 25% decrease in the distance between aqueous cylinders, the interaxial direction. There is little change in the interstitial direction, the direction toward the interstice equidistant from three aqueous cylinders. As the hexagonal phase is dehydrated, a number of internal changes in molecular lengths are described. Increases in the interaxial direction are much larger than in the interstitial. Simultaneously however, hydrocarbon chain lengths decrease, and polar group lengths increase. It is likely that molecules move axially and the cylinders become longer with dehydration. These dimensions and their changes might be used in the search for a better understanding of the energetics of molecular packing, of the interpretation of spectroscopic measurements of these phases, and of the mechanics of lipid layers.